1990
DOI: 10.1212/wnl.40.10.1509
|View full text |Cite
|
Sign up to set email alerts
|

Acute naming deficits following dominant temporal lobectomy

Abstract: Age at 1st risk for seizures may predict anomia following dominant anterior temporal lobectomy. We assessed confrontation naming before and 2 to 3 weeks after surgery in 45 right-handed patients grouped by side of focus and presence or absence of early (less than or equal to 5 years) risk factors. After left lobectomy, 6 of 10 (60%) patients with no early risks demonstrated significant decline (greater than or equal to 25%) in naming, but none of the patients with early risks showed this decline. After right l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
1
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 0 publications
7
65
1
2
Order By: Relevance
“…Stafiniak and colleagues (Stafiniak et al, 1990) demonstrated that post-operative anomia was predicted by relatively late age at first risk for seizures (defined as > 5 years). Subjects with early risk for seizures were less likely to show anomia following temporal lobectomy than those with no early risk.…”
Section: Age Of Onsetmentioning
confidence: 99%
“…Stafiniak and colleagues (Stafiniak et al, 1990) demonstrated that post-operative anomia was predicted by relatively late age at first risk for seizures (defined as > 5 years). Subjects with early risk for seizures were less likely to show anomia following temporal lobectomy than those with no early risk.…”
Section: Age Of Onsetmentioning
confidence: 99%
“…These techniques have included using the greatest decline for a right, non-language-dominant hemisphere resection as the level of significance (7) and a change exceeding 1 SD of the test measure (4,9,11). Hermann et al reported a subgroup of 7% to be at risk of dysnomia measured by VN, using the greatest decline for a patient undergoing right-sided nondominant hemisphere resection as the level of clinical significance, which was -10 in their patient group (7).…”
Section: Evaluation Of Nominal Speech Decline Risk For the Individualmentioning
confidence: 99%
“…However, acute naming deficits or a certain type of anomia is a common consequence of this standard left anterior temporal lobectomy. 13,22) Assessment of naming abilities of faces of familiar individuals in patients with epilepsy before and after anterior temporal lobectomy found that naming of photographed famous people was most impaired in patients who had undergone left anterior temporal lobectomy, whereas recognition of the identities of famous faces was not affected. 7) In their series, the anterior temporal cortex, amygdala, and anterior 1.5 to 3 cm of hippocampus were removed.…”
Section: Discussionmentioning
confidence: 99%
“…However, dominant anterior temporal lobectomy sometimes causes a severe naming deficit, despite the preservation of temporal language function. 10,11,22) Studies of braindamaged patients and functional magnetic resonance (MR) imaging data suggest that the anterior part of the left temporal lobe is extremely important in the retrieval of people's names. 3,12,24) In addition, proper name anomia is not rare as a complication of standard left anterior temporal lobectomy for epilepsy.…”
Section: Introductionmentioning
confidence: 99%